Analysis of the Effectiveness of Internal Supervision in Minimizing Problematic Financing in Murabahah Products (Study of BPRS Rajasa, Central Lampung) - Septia Novita Sari; Haris Santoso (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to describe the internal control system at BPRS Rajasa Lampung Tengah and analyze its effectiveness in minimizing non-performing financing (NPF) on murabahah products. A qualitative descriptive-analytical method was employed, with data collected through in-depth interviews, observation, and documentation. Primary data were obtained from management and marketing staff of BPRS Rajasa, while secondary data came from financing nominative reports and the NPF report as of December 2025. The findings reveal that BPRS Rajasa has implemented an internal control system through an independent internal audit unit conducting periodic file checks, collateral verification, and payment monitoring via a core banking system. Nevertheless, the NPF ratio as of December 2025 stood at 5.70%, exceeding OJK's 5% maximum threshold, with 257 out of 1,772 customers (14.49%) experiencing problematic financing: 40 in Special Mention, 48 Sub-standard, 64 Doubtful, and 145 in Loss category. Key challenges include inter-departmental miscommunication and weaknesses in initial customer selection. The internal control system is assessed as not yet fully effective, as it has been unable to reduce NPF below the regulatory threshold, though it has contributed to prevention and early detection of problematic financing.